2021
DOI: 10.1101/2021.10.04.463121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal characterization of circulating neutrophils uncovers distinct phenotypes associated with disease severity in hospitalized COVID-19 patients

Abstract: Multiple studies have identified an association between neutrophils and COVID-19 disease severity; however, the mechanistic basis of this association remains incompletely understood. Here we collected 781 longitudinal blood samples from 306 hospitalized COVID-19+ patients, 78 COVID-19- acute respiratory distress syndrome patients, and 8 healthy controls, and performed bulk RNA-sequencing of enriched neutrophils, plasma proteomics, cfDNA measurements and high throughput antibody profiling assays to investigate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…Conversely, IRF8 suppresses neutrophil generation (34). Consistent with this finding, increased absolute neutrophil counts have been associated with severe but not mild COVID-19 (35). These data are consistent with the notion that in mild patients, viral infection may directly stimulate appropriate selected ISGs responses, including CXCL10, and activate IFNa production that bridges innate and adaptive immunity through skewing DC differentiation/activation, towards the priming and expansion of Th1 cells, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, IRF8 suppresses neutrophil generation (34). Consistent with this finding, increased absolute neutrophil counts have been associated with severe but not mild COVID-19 (35). These data are consistent with the notion that in mild patients, viral infection may directly stimulate appropriate selected ISGs responses, including CXCL10, and activate IFNa production that bridges innate and adaptive immunity through skewing DC differentiation/activation, towards the priming and expansion of Th1 cells, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Third, in a recent study it was shown that dexamethasone treatment in COVID-19 patients affected circulating neutrophils, altered their IFN signaling and expanded immature neutrophils [87]. Similarly, increase in abnormal/immature neutrophils in the blood stream during severe COVID-19 has been observed by previous studies [20,22,27,53]. Whether the hyperinflammatory environment as well as dexamethasone treatment specifically effects the functional responses of these immature neutrophils against bacterial infection is largely unknown.…”
Section: Plos Pathogensmentioning
confidence: 82%
“…Altered myeloid cell expression states, including the accumulation of cells with hallmarks of myeloid-derived suppressor cells (MDSC), are consistent features in the blood of COVID-19 patients, and serve as a hallmark of severity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Monocytes and granulocytes associated with increased COVID-19 severity exhibit low expression of HLA-DR, and high expression of hallmark MDSC genes such as S100A12 (EN-RAGE), and can impair T cell activation via contactdependent (i.e., PD-L1) and soluble mechanisms, including IL-10, TGF-β, arginase 1, IDOdependent tryptophan metabolism, and reactive oxygen and nitrogen species (reviewed in [19][20][21][22] ).…”
Section: Introductionmentioning
confidence: 99%